The Efforts of the Kamsel Unit through Dikmaslantas to the Community in Order to Prevent Traffic Violations at the Tangerang City Police Station Metro - Farhandhani Abyanto (Indonesian Journal of Police Studies, 2021)
This research is motivated by the large population of Indonesia and the development of transportation technology, resulting in traffic problems, namely traffic violations. Traffic violations are caused by a lack of knowledge and understanding of the rules and ethics in good and correct driving. Efforts made to prevent traffic violations are focused on pre-emptive efforts, namely Dikmaslantas, where the purpose of Dikmaslantas is to provide knowledge and understanding of traffic to the public so that they know and understand good and correct traffic procedures. This research was conducted through a qualitative approach, using field research research methods. The concepts and theories used are the Effort Concept, the Dikmaslantas Concept, the Traffic Violation Concept, the Traffic Order Concept, management theory, and communication theory. Data collection techniques through interviews, observations, and document studies. Techniques of data analysis by means of data reduction, data presentation, and drawing conclusions. The results of the study found that traffic violations committed by the people of the city of Tangerang were still high. The efforts made by the Kamsel Unit through the Dikmaslantas are providing counseling to the community, making banners, billboards and banners, collaborating with relevant agencies, and collaborating with radio stations. The factors that influence the implementation of Dikmaslantas consist of supporting factors and inhibiting factors. Based on the results of the study, conclusions and suggestions from the author are increasing the number of personnel, increasing the budget, adding facilities and infrastructure. Added traffic lessons in schools so as to reduce traffic violations. The community can play an active role in minimizing the occurrence of traffic violations by complying with applicable laws and regulations.